The Perception of Japanese Language Education Students About Microteaching - Mardani, Desak Made Sri; Padmadewi, Ni Nyoman (Universitas Pendidikan Indonesia (Indonesia University of Education), 2020)
Microteaching is one of the subject matters to prepare student teachers. Many publications confirm the function and importance of microteaching in improving the student teachers’ teaching skills. However, publication on the perception of Japanese Language Education students about microteaching is still limited, despite its importance in guiding the students for better improvement. This study aimed at analyzing the students’ perception on the implementation of microteaching at the Japanese Language Education in a university in Bali on 2018. This study used qualitative research, and the data collected by questionnaire and interview. The results of the analysis showed that holistically, the students have postive perception and microteaching is perceived as very useful to improve the student teachers’ teaching skills. The instrumens used are not only relevant to assess the progress and the achievement of the student teachers but also can function as guideline for students on what to do in improving the teaching skills.